Acute kidney injury complicating bee stings – a review - da Silva, Geraldo Bezerra (Rev Inst Med Trop Sao Paulo, 2017)
Bee stings can cause severe reactions and have caused many victims in the last years. Allergic reactions can be triggered by a single sting and the greater the number of stings, the worse the prognosis. The poisoning effects can be systemic and can eventually cause death. The poison components are melitin, apamin, peptide 401, phospholipase A2, hyaluronidase, histamine, dopamine, and norepinephrine, with melitin being the main lethal component. Acute kidney injury (AKI) can be observed in patients suffering from bee stings and this is due to multiple factors, such as intravascular hemolysis, rhabdomyolysis, hypotension and direct toxicity of the venom components to the renal tubules. Arterial hypotension plays an important role in this type of AKI, leading to ischemic renal lesion. The most commonly identified biopsy finding in these cases is acute tubular necrosis, which can occur due to both, ischemic injury and the nephrotoxicity of venom components. Hemolysis and rhabdomyolysis reported in many cases in the literature, were demonstrated by elevated serum levels of indirect bilirubin and creatine kinase. The severity of AKI seems to be associated with the number of stings, since creatinine levels were higher, in most cases, when there were more than 1,000 stings. The aim of this study is to present an updated review of AKI associated with bee stings, including the currently advised clinical approach.